Application of the Delphi Method for the inclusion of externalities in occupational safety and health analysis (2016)
Organizations should regularly conduct an assessment of their occupational hazards in order to design and implement preventive measures that are necessary and sufficient to deal with the level of risk, the costs of prevention and the safety at levels considered acceptable by the organization. Furthermore, the selection of measures to be implemented in an organization should take into account both internal and external costs. Externalities are of great importance in terms of the costs of accidents at work; nevertheless, they are not often properly addressed by the organizations. In this paper we describe an application of the Delphi method to understand how externalities can be included in Occupational Safety and Health.